Pengaruh Metode Card Sort Dalam Meningkatan Hasil Belajar Al Qur’an Hadits Siswa Kelas IV di Madrasah Ibtidaiyah Muhammadiyah 07 Sidokelar Paciran - Sintiya Mafazatin; M. Chotibuddin (STIT Muhammadiyah Paciran, 2022)
The purpose of this study was to improve student learning outcomes for the fourth grade Al-Qur’an Hadith subjects through the Card Sort method at MI Muhammadiyah 07 Sidokelar.This study uses quantitative methods with parametric statistical data analysis techniques, and uses a one-group pretest posttest design. This research was conducted at MI Muhammadiyah 07 Sidokelar in the even semester of the 2020/2021 school year. The selected population is class IV with a total of 17 people. From that population, samples were taken using a saturated sampling technique (if the population is less than 30) then the sample was class IV students of MI Muhammadiyah 07 Sidokelar Paciran as many as 17 people. The data collection instruments used were observation and test methods.In the presentation of the acquisition value in the observation of learning activities using the card sort method, an average value of 81.81% was obtained, this means that the card sort method in learning can be implemented well. While the test results data that have been collected were analyzed using validity test techniques, reliability tests, normality tests, homogeneity tests, and strengthened using product moment correlation tests, as well as significance tests or t-tests (t-test). From the results of the data analysis that has been carried out, there is a significant correlation between the X variable and the Y variable. As indicated by the correlation coefficient rcount of 0.864 and rtable of 0.514, rcount > rtable (0.864 > 0.514). And based on the results of the significance test or t-test (t-test) obtained a tcount value of 6.648 and a t-table value of 2.131. Then tcount > ttable (6,648 > 2,131). So it can be concluded that H0 is rejected and Ha is accepted. So the card sort method has an effect on increasing student learning outcomes in the subjects of Al Qur’an Hadith on the legal material of idgham and iqlab reading in class IV MI Muhammadiyah 07 Sidokelar Paciran for the 2020/2021 school year.Furthermore, the calculation is carried out using the coefficient of determination formula to find out how big the contribution of the influence of variable X to variable Y. Using the formula KP = r2 x 100%, the results obtained are 74.6% of the contribution of variable X to variable Y.